Merry Science of Literature (Almost an Essay) - Tūtlytė, Rita (Literatūra, 2021)
The article investigates the development of the literary studies of Lithuanian literature over the past three decades pointing out some mental movements as well as difficulties of „transferrence“ and „hermeneutics“ of selfreflection. The article is not focused on describing all the schools of literary studies that were under formation at that time, the translated theoretical works or on classifying the researchers of the period (some names are mentioned sporadically as an example only). The aim is to give just one perspective without aiming to provide an objective wholsome overwiew.